Tackling Obesity via Workplace Health Promotion - Woolmer, Jillian; Snell, Robynne; Howat, Peter; Sauer, Kay (2005)
The Curtin University Healthy Lifestyle Program is a worksite health promotion program that has been advocating a healthy supportive environment by encouraging healthy behaviours for 20 years. A multifaceted approach has been used with an Accredited Practising Dietitian available for one-to-one dietary consults with staff and an email newsletter "Eat for Life" distributed to staff which focused on healthy lifestyle changes such as choosing healthy food more often and increasing physical activity, and environmental changes to make healthy choices easier on campus. The staff restaurant and student guild catering outlets agreed to modify their menus, based on recommendations made by staff and students in the Nutrition Program and provided more healthy food choices.In 2003 a weekly weightloss support group was introduced. Lunchtime seminars attracted interest in the group while also raising awareness of the need to eat healthy food and increase physical activity especially walking. Participants liked the group sessions as they "kept you on track","learnt from other's tips and pitfalls" and gained extra support from other staff at work and the Curtin Healthy Lifestyle Program. Two star participants lost 20kg each over a year via their new healthier lifestyle.